Exploring the Bank-Specific and Macroeconomic Determinants of Capital Structure: Evidence from Nepalese Commercial Banks - Purna Man Shrestha,; Rajesh Gurung, (Pravaha, 2023)
Background: Capital structure, i.e., the mixture between borrowed funds and shareholders’ equity of a firm, is the major concern of financial management. It is affected by several internal and external factors. A firm's capital structure performs vital contribution in shaping profitability. Every firm must identify the factors influencing its capital structure. Objectives: This research focuses on identifying the key drivers of the capital structure of Nepalese commercial banks using profitability (ROA), bank size [Ln(TA)], and liquidity (LIQ) as bank-specific variables, actual gross domestic product (GDP) growth rate, inflation (INF), and interest rate (IR) as macroeconomic independent variables, and the leverage as dependent variable as a proxy for capital structure. Methodology: A pooled OLS, fixed effect, and random effect regression model is used to examine the annual panel data of twenty commercial banks operating in Nepal from 2014 to 2023. Main Findings: This paper finds the considerable role of bank-specific and macroeconomic variables in determining the mixture of debt and equity of a firm. The capital structure of Nepalese commercial banks is negatively impacted by profitability and liquidity, whereas it is positively impacted by bank size. Furthermore, it is positively influenced by the GDP growth rate and inflation and adversely influenced by the interest rate. Conclusion: This paper concludes that profitable commercial banks with higher liquidity heavily depend on equity capital rather than debt capital. On the other hand, larger banks tend to use more debt. It is further concluded that as economic growth becomes strong with lower interest rates, Nepalese commercial banks tend to use more debt.